A small molecule inhibitor of mutant IDH2 rescues cardiomyopathy in a D‐2‐hydroxyglutaric aciduria type II mouse model. Issue 6 (28th July 2016) - Wang, Fang; Travins, Jeremy; Lin, Zhizhong; Si, Yaguang; Chen, Yue; Powe, Josh; Murray, Stuart; Zhu, Dongwei; Artin, Erin; Gross, Stefan; Santiago, Stephanie; Steadman, Mya; et al.
Abstract: D‐2‐hydroxyglutaric aciduria (D2HGA) type II is a rare neurometabolic disorder caused by germline gain‐of‐function mutations in isocitrate dehydrogenase 2 ( IDH2 ), resulting in accumulation of D‐2‐hydroxyglutarate (D2HG). Patients exhibit a wide spectrum of symptoms including cardiomyopathy, epilepsy, developmental delay and limited life span. Currently, there are no effective therapeutic interventions. We generated a D2HGA type II mouse model by introducing the Idh2R140Q mutation at the native chromosomal locus. Idh2R140Q mice displayed significantly elevated 2HG levels and recapitulated multiple defects seen in patients. AGI‐026, a potent, selective inhibitor of the human IDH2R140Q‐mutant enzyme, suppressed 2HG production, rescued cardiomyopathy, and provided a survival benefit in Idh2R140Q mice; treatment withdrawal resulted in deterioration of cardiac function. We observed differential expression of multiple genes and metabolites that are associated with cardiomyopathy, which were largely reversed by AGI‐026. These findings demonstrate the potential therapeutic benefit of an IDH2R140Q inhibitor in patients with D2HGA type II.